Exploration: Creative Thinking Skills in Writing Essays Media-Based Image Series - Ayu, Nidya; Suharno; Chrysti Suryandari, Kartika (Universitas Pendidikan Ganesha, 2023)
Creative thinking is an essential skill in learning for students. Students can think creatively by showing new ways of thinking, daring to compile questions and likely answers, and giving new ideas. In addition, this study aims to analyses creative thinking skills using a series of image media. This research uses descriptive qualitative research with a case study model. The subjects of this study were grade III students numbering 50 students. This research method uses interviews to follow up on these findings. Interviews were conducted to find out the problems that occurred. The interview used is structured. Data analyses in this study used the theory of Miles and Huberman. The results of the overall research and creative thinking skills in writing essays with series image media still have to be re-evaluated. The students seemed to have trouble getting ideas into narrative-based writing. This will result in learning to write narratives that are hampered. In general, it is proven that more than half of the sample numbers of students still do not meet the four aspects of creative thinking indicators, so it will undoubtedly hinder the learning process in the classroom, especially related to writing skills. This research implies that it is hoped that all stakeholders will be able to realize the importance of creative thinking skills early by training students using series image media or others.